2022
DOI: 10.1021/acs.jpclett.2c02694
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electron Transfer Enables Highly Efficient Dual Emission Modes of Mn2+-Doped Cs2Na1–xAgxBiCl6 Double Perovskites

Abstract: Double perovskites with bright emission, low toxicity, and excellent stability have drawn considerable attention. Herein, we report the hydrothermal synthesis of Mn2+-doped Cs2Na1–x Ag x BiCl6 double perovskites that exhibit dual emission modes. Introducing Ag+ ions to Cs2NaBiCl6 samples enables a bright self-trapped exciton (STE) emission in orange-red color, whereas Mn2+ dopants induce a yellow-orange emission. Importantly, Mn2+ doping into Cs2Na1–x Ag x BiCl6 double perovskites with an indirect bandgap enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…PL measurements showed that immediately following the postsynthetic doping reaction (before the aging process), the Mn-emission peak was observed to be at 660 nm, redder than the typical Mn-emission peak range of 590−620 nm, indicating the DP NCs with inhomogeneous surface-doped Mn 2+ ions. 29,31,43 The Mn-emission peak then blue-shifted from 660 to 630 nm during the subsequent aging process, implying an internalization of Mn 2+ cations through an entropy-driven inward diffusion process as previously reported for the Mn 2+doped CsPbCl 3 perovskite NCs (Figure 2A,B). 32 The onsite Mn 2+ inward diffusion process was further confirmed by timeresolved PL spectroscopy measurements (Figure 2C).…”
Section: T H Isupporting
confidence: 77%
See 1 more Smart Citation
“…PL measurements showed that immediately following the postsynthetic doping reaction (before the aging process), the Mn-emission peak was observed to be at 660 nm, redder than the typical Mn-emission peak range of 590−620 nm, indicating the DP NCs with inhomogeneous surface-doped Mn 2+ ions. 29,31,43 The Mn-emission peak then blue-shifted from 660 to 630 nm during the subsequent aging process, implying an internalization of Mn 2+ cations through an entropy-driven inward diffusion process as previously reported for the Mn 2+doped CsPbCl 3 perovskite NCs (Figure 2A,B). 32 The onsite Mn 2+ inward diffusion process was further confirmed by timeresolved PL spectroscopy measurements (Figure 2C).…”
Section: T H Isupporting
confidence: 77%
“…Codoping more than one type of cation into DP NCs has garnered significant attention recently due to the potential optoelectronic property enhancements that can be achieved. ,, In particular, recent studies have demonstrated that Na + doping into DP NCs can improve the stability of the materials by raising the energetic barrier for halide vacancy diffusion and can enhance the PL through breaking the symmetry of octahedral sublattice units and reducing the density of surface trap states. ,, To evaluate the Na + doping effect in our system, we expanded our postsynthetic strategy to codoping Na + and Mn 2+ cations into the Cs 2 AgInCl 6 DP NCs.…”
Section: Resultsmentioning
confidence: 99%
“…[83,146] Stability can be greatly improved by self-assembly from stable low-dimensional metal-halide perovskite nanocrystals such as Cs 2 MX 6 (M = Sn, Zr, Te, Hf; X = Cl, Br, I), also circumventing the lead toxicity issues for CsPbX 3 . [147][148][149][150][151][152][153] Another concern is the modulation of emission wavelength in perovskite nanocrystal superlattices. Although visible light emission has been widely reported in perovskite nanocrystal superlattices, violet, UV, and near-infrared (NIR) emissions have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[ 83,146 ] Stability can be greatly improved by self‐assembly from stable low‐dimensional metal–halide perovskite nanocrystals such as Cs 2 MX 6 (M = Sn, Zr, Te, Hf; X = Cl, Br, I), also circumventing the lead toxicity issues for CsPbX 3 . [ 147–153 ]…”
Section: Discussionmentioning
confidence: 99%
“…When I 527 /I 485 is less than 1, the emission peak intensity at 527 nm is higher than that at 485 nm, and the more luminescent centers related to 527 nm emission can provide more holes to recombine with electrons from the excited state associated with 485 nm emission, thus reducing non-radiative transition and leading to higher QY. 48,49 When I 527 /I 485 exceeds 1, the insufficient electrons from the excited state associated with 485 nm emission restrain the charge transfer, resulting in an increase of nonradiative transition and a decrease of QY. In short, the value of I 527 /I 485 influences the charge transfer in different fluorescence centers, and further changes the QY of CDs.…”
Section: Optical Propertiesmentioning
confidence: 99%